Analisis Penawaran Kredit Modal Kerja dan Pengaruhnya Terhadap Pertumbuhan Ekonomi: Pendekatan Panel Simultan (Studi Bank BUKU-4 di Indonesia 2012-2020) - Jayadiadha, Karina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This paper explores the contribution of working capital credit to economic growth in Indonesia. Therefore, through this paper with data between 2012 first quarter to fourth quarter 2020 was attempted to prove the simultaneous relationship between working capital credit and economic growth, evidence in BUKU-4 Banks in Indonesia. Simultaneous relationship is inseparable from the exogenous (instrument) variables that affect the supply of working capital credit and economic growth. The financial performance used proxy variables such as CAR, LDR, ROA, NPL, and Interest Rates. While real GDP is used as a proxy for economic growth. The method in this research used Panel Model and Two Stage Least Square. Panel model is used to find heterogeneity in BUKU-4 Banks, while Two Stage Least Square is used to detect the simultaneous relationship between endogen variables, influenced by instruments variable. However, the findings reveal that between 2012Q and 2020Q4, working capital credit and economic growth has a simultaneous relationship. Meanwhile, Solow’s theory can be proven by the key role of working capital credit by BUKU-4 Banks to stimulating the economic growth in Indonesia. Moreover, our findings suggest in the midst of uncertainty due to Covid-19, BUKU-4 Banks must strive to improve risk mitigation, improve the quality of regulations, while maintaining the performance.Key words: working capital credit, real GDP, simultaneous, BUKU-4 Banks.